Resistance to Vesicular Stomatitis Virus Infection Requires a Functional Cross Talk between the Eukaryotic Translation Initiation Factor 2α Kinases PERK and PKR - Baltzis, Dionissios (American Society for Microbiology, 2004)
Phosphorylation of the alpha (α) subunit of the eukaryotic translation initiation factor 2 (eIF2) leads to the inhibition of protein synthesis in response to diverse stress conditions, including viral infection. The eIF2α kinase PKR has been shown to play an essential role against vesicular stomatitis virus (VSV) infection. We demonstrate here that another eIF2α kinase, the endoplasmic reticulum-resident protein kinase PERK, contributes to cellular resistance to VSV infection. We demonstrate that mouse embryonic fibroblasts (MEFs) from PERK(−/−) mice are more susceptible to VSV-mediated apoptosis than PERK(+/+) MEFs. The higher replication capacity of VSV in PERK(−/−) MEFs results from their inability to attenuate viral protein synthesis due to an impaired eIF2α phosphorylation. We also show that VSV-infected PERK(−/−) MEFs are unable to fully activate PKR, suggesting a cross talk between the two eIF2α kinases in virus-infected cells. These findings further implicate PERK in virus infection, and provide evidence that the antiviral and antiapoptotic roles of PERK are mediated, at least in part, via the activation of PKR.